“Para mim, linguagem é a forma como a criança se expressa!”: o papel da linguagem na educação infantil a partir de entrevistas e planejamentos de professoras de uma rede privada - Duart, Patrícia Prates de Quadros (Universidade do Vale do Rio dos Sinos, 2023)
Early Childhood Education, the first stage of basic education, is an important space for the construction of learning. By providing pedagogical strategies for interactions between adults and children, permeated and mediated by the use of language, one contributes to education in its entirety and to the constitution of these subjects. In view of this demand and with the purpose of looking at language in this context, this study aims to analyze how language is highlighted in the speech and lesson planning of kindergarten teachers from a private school in the metropolitan area of Porto Alegre, during the pandemics. To this end, the data were generated during meetings and semi-structured interviews with regular kindergarten teachers from the collaborating institution. Documents such as educators' lesson plans which related the BNCC (Brazilian National Curricular Base, BRASIL, 2017) and the DCNEI (Brazilian Norms for Early Childhood Education, BRASIL, 2010) guidelines were also considered. The respective data were analyzed from the perspective of studies focused on language development (BAKTHIN/VOLOCHINOV, 2006; VYGOSTSKY, 2007; PERFEITO, 2007; VEÇOSSI, 2014; STAUDT, 2015; STAUDT; FRONZA, 2015; SACCOMANI, 2018, and others). Among the findings of this dissertation, it stands out that, in the Early Childhood Education context in focus, language is treated as one of the aspects to be developed by teachers, thus playing an important role in the developmental process of the child. Although with different perceptions about language and its approaches, it is possible to notice that, as learning mediators, the teachers recognize the need to identify, in each pedagogical strategy, interactive situation and exchange relationship, opportunities for the development of children's language competences. As language is neither static nor restricted, all interaction possibilities are permeated by its use and there will always be opportunities for incentives and stimuli to learning. Language, therefore, assumes an important role in the context of learning mediations in Early Childhood Education, because it empowers the different subjects that use it, recognize and constitute themselves in the other(s).
Keywords: Educação infantil; Desenvolvimento da linguagem; Pandemia; Early childhood education; Language development; Pandemics; ACCNPQ::Lingüística, Letras e Artes::Lingüística